Palpi aplenty: new species in the Chrysotus longipalpus species group (Diptera: Dolichopodidae) - Runyon, Justin B.; Capellari, Renato S. (Zootaxa, 2018)
Four new Nearctic species belonging to the Chrysotus longipalpus species group are described: Chrysotus keyensis sp. nov. (Florida), Chrysotus mccreadiei sp. nov. (Alabama), Chrysotus mystax sp. nov. (Alabama), and Chrysotus plumarista sp. nov. (Alabama). This brings the number of known species in this group to twelve. A key to species of males of the C. longipalpus species group and new distribution records are provided.